Fiber laser at 2 micron region using double-clad thulium/ytterbium co-doped yttria-alumino-silicate fiber - Harun, Sulaiman Wadi; Saidin, Norazlina; Damanhuri, Siti Sarah Ahmad; Ahmad, Harith; Halder, Arindam; Paul, Mukul Chandra; Das, S.; Pal, Mrinmay; Bhadra, Shyamal Kumar (IOP Publishing, 2011)
A lasing action from a newly developed double-clad Tm3+/Yb3+ co-doped yttria-alumino-silicate fiber (TYDF) is demonstrated based on cladding pumping technique. The TYDF used was drawn from D-shape preform, which was fabricated using a modified chemical vapor deposition (MCVD) process in conjunction with a solution doping technique. The Tm3+and Yb3+ ions concentrations in this fiber are 5.55×1019 and 15.52×1019 ions/cc, respectively. The fiber laser operates at wavelength of 1948.4 and 1947.2 nm with pump power thresholds of 0.6 and 1.0 W for 915 and 940 nm pumping, respectively. The maximum output power of 10.5 mW was achieved with the 915 nm pumping at the maximum pump power of 1.5 W. It is found that the laser is more efficient with 915 nm pumping compared to 940 nm pumping.